Identification of the Putative Tumor Suppressor Characteristics of FAM107A via Pan-Cancer Analysis - Ou, Dehua; Zhang, Zhiqin; Wu, Zesong; Shen, Peilin; Huang, Yichuan; She, Sile; She, Sifan; Lin, Ming-en (Frontiers in Oncology, 2022)
Family with sequence similarity 107, member A(FAM107A) was supposed as a tumor suppressor for various types of tumors. However, no pan-cancer analysis of FAM107A is available. Therefore, we conducted a FAM107A-related pan-cancer analysis across thirty-three tumors based on TCGA database to explore the molecular characteristics of FAM107A. The FAM107A expression is reduced in most cancers, and its down-regulated expression was linked to poor overall survival and progression-free survival of tumor patients. Analysis of DNA methylation of FAM107A gene showed a negative correlation between FAM107A expression and promoter methylation in numerous cancers. Furthermore, FAM107A expression was noted to be involved in myeloid-derived suppressor cells infiltration in multiple cancers. To explore the mechanism of FAM107A in cancers, KEGG and GO enrichment analysis was performed and the result showed “Cell adhesion” and “cAMP signaling pathway” terms as the potential impact of FAM107A on cancers. An experiment in vitro showed FAM107A knockdown promoted the proliferation, migration and invasion of bladder cancer and renal cancer cells. Our study indicates that FAM107A may be a putative tumor suppressor in bladder cancer and other tumors.